Cultural adaptation and psychometric validation of the Portuguese breakthrough pain assessment tool with cancer patients - Bernardes, S. F. (2021)
Breakthrough cancer pain (BTcP) is a transient exacerbation of pain that occurs over persistent, stable, and adequately controlled cancer background pain. It is prevalent and bears severe consequences to patients' quality-of-life. The effective management of BTcP depends on fast and reliable (re)assessment. The Breakthrough pain Assessment Tool (BAT) is one of the most concise and reliable self-report instruments adapted to clinical contexts so far, showing good psychometric qualities in the United Kingdom, the Netherlands, and South Korea. As to promote the effective management of BTcP in Portuguese-speaking communities this study, first aimed to culturally adapt and validate the Portuguese version of the BAT (BAT-Pt). Second, and most importantly, it sought to provide novel evidence on its criterion validity by investigating its association with measures of psychological distress, which has not been yet investigated. The BAT was translated into European Portuguese, using the back-translation method, and culturally adapted. Its psychometric properties (factor structure, internal consistency, construct and criterion validity) were analyzed in a cross-sectional multicenter study, with a sample of 65 cancer patients (49.2% women) recruited from eight hospitals in mainland Portugal (a priori power analysis determined a minimum sample of 50). Health professionals collected patients' clinical information, assessed their functional disability (ECOG Performance Status) and the adequacy of pain control. In addition to the Portuguese version of the BAT (BAT_Pt), patients completed the Portuguese versions of the Brief Pain Inventory, the Hospital Anxiety and Depression Scale, a Distress Thermometer and answered questions about the adequacy of pain control. The BAT-Pt was very well accepted by experts and patients. As hypothesized, a Principal Axis Factor Analysis revealed two underlying factors accounting for 55.2% of the variance: (1) Pain Severity and Impact of BTcP and (2) Duration of BTcP and Medication Inefficacy. Two items (on episode frequency and medication efficacy) were analyzed separately given their lower/cross loadings. The BAT-Pt showed good internal consistency overall (?=0.79) and for each sub-scale, namely, Pain Severity and Impact of BTcP (n=5 items; ?=0.86) and Duration of BTcP and Medication Inefficacy (n=2 items; rsb=0.62).